IMF Survey, Volume 31, Issue 19. (IMF Survey; IMF Survey, 2002)
Improving market access for developing countries is one of the most important steps that rich countries can take in fighting global poverty, according to the chief economists of the World Bank and the IMF. Both institutions highlighted the issue during their recent Annual Meetings. Market access was the theme of a joint report and press conference, and a seminar.